A Bibliometric Analysis of the Literature on Optimum Currency Areas and Monetary Integration - Ntombi Matonana; Andrew Phiri (Managing Global Transitions)
Our study presents a pioneering bibliometric analysis of optimum currency areas literature and monetary integration, utilising 9,228 research outputs published between 1960 and 2022. We employ the biblioshiny function in R-studio to comprehensively analyse this data. Our findings reveal a growing body of literature on optimum currency areas, with increased author productivity. Remarkably, influential authors, despite their lower research volume, receive extensive citations and publish in prestigious journals such as The Quarterly Journal of Economics and The American Economic Review. Additionally, our analysis exposes a lack of representation from non-European/American institutions, as well as an underrepresentation of female and non-White researchers. We propose future research directions to address these gaps. Notably, our study is the first to conduct a bibliometric analysis on optimum currency areas and monetary integration, highlighting its originality.